PERAN KOMPLEKS JUKSTAGLOMERULUS TERHADAP RESISTENSI PEMBULUH DARAH - Toreh, Renny M.; Kalangi, Sonny J.R.; Wangko, Sunny (UNIVERSITAS SAM RATULANGI, 2012)
Abstract: As the main structural component of the renin-angiotensin-aldosterone system (RAAS), the juxtaglomerular complex plays a very important role in the regulation of vascular resistance. The synthesis and release of renin into the circulation occurs due to the decrease of blood pressure, loss of body fluid, and a decrease of sodium intake. Renin converts angiotensinogen into angiotensin I, which is further converted by the angiotensin converting enzyme (ACE) into angiotensin II. This angiotensin II causes vasoconstriction of blood vessels, resulting in an increase of vascular resistance and blood pressure. The ACE inhibitors and the angiotensin receptor blockers (ARBs) do not inhibit the RAAS completely since they cause an increase of renin activity. The renin blockers are more effective in inhibiting RAAS activity; therefore, these renin blockers can be applied as antihypertensive agents with fewer side effects. The RAAS activity can be inhibited by a decrease of renin synthesis in the juxtaglomerular complex by blocking the signals in the juxtaglomerular complex that stimulate renin synthesis, and by blocking the gap junctions in the juxtaglomerular complex. Keywords: juxtaglomerular complex, vascular resistance, RAAS.Â Â Abstrak: Kompleks jukstaglomerulus sebagai komponen struktural utama sistem renin angiotensin berperan penting dalam pengaturan resistensi pembuluh darah. Sintesis dan pelepasan renin ke sirkulasi terjadi karena tekanan darah yang rendah, kehilangan cairan tubuh, dan kurangnya intake natrium. Renin akan memecah angiotensinogen menjadi angiotesin I yang kemudian secara cepat dikonversi oleh enzim pengonversi angiotensinÂ menjadi angiotensin II. Angiotensin II menyebabkan vasokontriksi pembuluh darah sehingga meningkatkan resistensi pembuluh darah yang pada akhirnya akan meningkatkan tekanan darah. ACEinhibitor dan ARB kurang sempurna dalam menghambat kerja SRAA oleh karena keduanya memutuskan rantai mekanisme timbal balik sehingga meningkatkan aktifitas renin. Penghambat renin lebih efektif digunakan untuk menghambat aktifitas SRAA sehingga penghambat renin dapat digunakan sebagai obat anti-hipertensi dan memiliki efek samping yang rendah. Metode penghambatan SRAA yang juga dapat dikembangkan ialah penghambatan sintesis renin dalam kompleks jukstaglomerulus dengan cara menekan sinyal-sinyal dalam kompleks jukstaglomerulus yang merangsang sintesis renin dan menghambat fungsi taut kedap yang terdapat dalam kompleks jukstaglomerulus. Kata kunci: kompleks juksta glomerulus, resistensi vaskular, SRAA.